Factors Influencing Career Development of High School Students: A Systematic Literature Analysis - Bunga Afasli; Ifdil; Daharnis (Manajia: Journal of Education and Management, 2025)
Career development of senior high school students is an important aspect in shaping their readiness to face the world of work. However, many factors influence how students develop their careers, both in terms of internal and external factors. This article aims to analyze the factors that influence the career development of senior high school students through a systematic literature review (SLR) approach. This method is used to identify, evaluate, and synthesize findings from 10 relevant studies consisting of 5 international articles and 5 national articles. The studies were selected based on criteria of suitability with the topic and methodology used. The results of the analysis indicate that the main factors influencing the career development of senior high school students include family support, school involvement, socio-cultural factors, personal motivation, and access to career information and training. Based on these findings, it can be concluded that a holistic approach involving various parties is essential in students' career development. Further studies are expected to identify more effective strategies in strengthening career development among senior high school students.